Effects of early neonatal massage with therapeutic positioning in preterm and low birth weight babies on neurobehavioral and neurodevelopmental status - RAGURAMAN RAJARAM,; D. MALAR VIZHI,; V.P.R.SIVA KUMAR, (International Journal of Pharma and Bio Sciences, 2017)
Background: India has the greatest number of premature infants and low birth weight population. Infant massage and therapeutic positioning has been documented for several decades to have a positive effect on preterm and low birth weight infants. Objective of the study was to determine the effects of early neonatal massage with therapeutic positioning in preterm and low birth weight babies on neurobehavioral and neurodevelopmental status. Methodology: Study design was quasi experimental, thirty preterm (32-37 weeks) and low birth neonates (1.5-2.5kg) were recruited. Infant Massage with therapeutic positioning was administered to the subjects for eight weeks after taking baseline Neonatal Neuro behavioral Examination (NNE) and Infant Neurological International Battery (INFANIB) scores. Comparison was made between pre and post NNE and INFANIB scores. Results: Findings of the study showed significant difference between pre and post NNE and INFANIB scores (p < 0.05). There was significant correlation between chronological age with NNE(r = 0.557, p < 0.05) and INFANIB (r = 0.442, p < 0.05) baseline scores, however gestational age and birth weight were not significantly correlated (p <.05). Conclusion: The study concluded that neonatal massage and therapeutic positioning have significant effects in improving neurobehavioral and neuro development in preterm and low birth weight babies.